Discovery of the Pseudomonas Polyyne Protegencin by a Phylogeny-Guided Study of Polyyne Biosynthetic Gene Cluster Diversity - Alex J. Mullins (American Society for Microbiology, 2021)
ABSTRACT Natural products that possess alkyne or polyyne moieties have been isolated from a variety of biological sources and possess a broad a range of bioactivities. In bacteria, the basic biosynthesis of polyynes is known, but their biosynthetic gene cluster (BGC) distribution and evolutionary relationship to alkyne biosynthesis have not been addressed. Through comprehensive genomic and phylogenetic analyses, the distribution of alkyne biosynthesis gene cassettes throughout bacteria was explored, revealing evidence of multiple horizontal gene transfer events. After investigation of the evolutionary connection between alkyne and polyyne biosynthesis, a monophyletic clade was identified that possessed a conserved seven-gene cassette for polyyne biosynthesis that built upon the conserved three-gene cassette for alkyne biosynthesis. Further diversity mapping of the conserved polyyne gene cassette revealed a phylogenetic subclade for an uncharacterized polyyne BGC present in several Pseudomonas species, designated pgn. Pathway mutagenesis and high-resolution analytical chemistry showed the Pseudomonas protegens pgn BGC directed the biosynthesis of a novel polyyne, protegencin. Exploration of the biosynthetic logic behind polyyne production, through BGC mutagenesis and analytical chemistry, highlighted the essentiality of a triad of desaturase proteins and a thioesterase in both the P. protegens pgn and Trinickia caryophylli (formerly Burkholderia caryophylli) caryoynencin pathways. We have unified and expanded knowledge of polyyne diversity and uniquely demonstrated that alkyne and polyyne biosynthetic gene clusters are evolutionarily related and widely distributed within bacteria. The systematic mapping of conserved biosynthetic genes across the available bacterial genomic diversity proved to be a fruitful method for discovering new natural products and better understanding polyyne biosynthesis. IMPORTANCE Natural products bearing alkyne (triple carbon bond) or polyyne (multiple alternating single and triple carbon bonds) moieties exhibit a broad range of important biological activities. Polyyne metabolites have been implicated in important ecological roles such as cepacin mediating biological control of plant pathogens and caryoynencin protecting Lagriinae beetle eggs against pathogenic fungi. After further phylogenetic exploration of polyyne diversity, we identified a novel gene cluster in Pseudomonas bacteria with known biological control abilities and proved it was responsible for synthesizing a new polyyne metabolite, protegencin. The evolutionary analysis of polyyne pathways showed that multiple biosynthetic genes were conserved, and using mutagenesis, their essentiality was demonstrated. Our research provides a foundation for the future modification of polyyne metabolites and has identified a novel polyyne, protegencin, with potential bioactive roles of ecological and agricultural importance.